Relasi preferensi mahasiswa terhadap keterlibatan pengguna pada sosial media perpustakaan perguruan tinggi - Alinda Nindayuputri; Ganggi, Roro Isyawati Permata (Daluang: Journal of Library and Information Science, 2025)
Purpose. This study aims to determine the extent of the relationship between undergraduate students’ preferences and user engagement on the Instagram account @perpus.undip of Diponegoro University Library. Methodology. This research employs a quantitative approach. Data were collected through a questionnaire distributed to 100 respondents. The collected data were analyzed using correlation analysis with the help of SPSS version 26. Results and discussion. The findings indicate a moderate positive correlation between undergraduate students’ preferences and user engagement on the @perpus.undip Instagram account, with a correlation coefficient of 0.623. This suggests that students’ preferences are generally aligned with the engagement strategies employed on the library’s social media, although several aspects still require improvement to enhance overall user interaction. Conclusions. The study concludes that there is a positive and consistent relationship between library users’ preferences and user engagement on Diponegoro University Library’s Instagram account (@perpus.undip), as evidenced by a correlation coefficient of 0.623.